2018
DOI: 10.1109/tc.2018.2790394
|View full text |Cite
|
Sign up to set email alerts
|

PerfBound: Conserving Energy with Bounded Overheads in On/Off-Based HPC Interconnects

Abstract: Energy and power are key challenges in high-performance computing. System energy efficiency must be significantly improved, and this requires greater efficiency in all subcomponents. An important target of optimization is the interconnect, since network links are always on, consuming power even during idle periods. A large number of HPC machines have a primary interconnect based on Ethernet (about 40% of TOP500 machines), which, since 2010, has included support for saving power via Energy Efficient Ethernet (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…To distinguish these two kinds of Wakeup, we refer to the Wakeup of the FW mode as FW Wakeup, and that of the DS mode as DS Wakeup. The simulation results of [11]- [14] showed that the combination of the DS mode and the FW mode can help the 100G EEE interface to save more power than the DS mode only.…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish these two kinds of Wakeup, we refer to the Wakeup of the FW mode as FW Wakeup, and that of the DS mode as DS Wakeup. The simulation results of [11]- [14] showed that the combination of the DS mode and the FW mode can help the 100G EEE interface to save more power than the DS mode only.…”
Section: Introductionmentioning
confidence: 99%